Effect of sub-lethal nitrite toxicity on the hematological parameters of fingerlings of rohu, Labeo rohita (Ham.) - Das, P C; Ayyappan, S; Jena, J K; Das, B K (Indian Journal of Fisheries, 2011)
Changes in hematology of fingerlings of Labeo rohita exposed to 0, 1, 2, 4, 8 and 10.4 mg/l nitrite-nitrogen was studied for a period of 96 hours. Immature erythrocytes count, after 96 hours, increased with increasing concentration up to 4 mg/l followed by reduction to complete absence in 8-10.4 mg/l. Totalerythrocyte count reduced at 6 hour after which it increased continuously in 1- 2 mg/l, but reverse was the case in 4-10.4 mg/l. Haemoglobin content reduced with increasing concentration as well as exposure period, with significantreduction after 6, 12 and 24 hours in 10.4, 4-8 and 1-2 mg/l, respectively. Leukocyte count increased with exposure period in 4-10.4 mg/l with significant increase in 10.4, 8 and 4 mg/l after 6, 12 and 48hr., respectively. Blood glucose level increased with increasing exposure period with a peak after 6 hours proportional to the nitrite concentration. Serum protein content reduced insignificantly (P>0.05) after 96 hours with increasing nitrite concentration